The Tradition of Saint Patrick’s Purgatory between Visionary Literature and Pilgrimage Reports - Giovanni Paolo Maggioni (Universitat de Girona; Universitat Autònoma de Barcelona, 2017)
Saint Patrick’s Purgatory on Lough Derg is one of the most important pilgrimage sites in Western Europe. The tradition of the Purgatory is strictly connected with the diffusion of a text, the Tractatus de Purgatorio sancti Patricii, composed in the last part of the twelfth century, which tells of an Otherworld journey undertaken physically by a living person after having crossed a geographical threshold located in Ireland. This treatise, however, does not explicitly mention any recognizable place on the Irish isle. On the other hand, there exist accounts of a pilgrimage ritual a few years later in a place that can be identified as an island (or two) on the Lough Derg in the North of Ireland. In other words, in the tradition of Saint Patrick’s Purgatory, the primary literary text originated and developed independently from a given place, just as the ritual of pilgrimage to the Purgatory was independent from a given text. But both the text and pilgrimage came together in Avignon around 1353, from which time both textual traditions and pilgrimage reports began to interact and modify each other, inspiring and shaping new texts and new ritual forms, while creating fictional characters derived from historical figures and, conversely, portraying literary characters as historical figures.